Entrepreneurial mindfulness and organizational resilience of Chinese SMEs during the COVID-19 pandemic: The role of entrepreneurial resilience - Liu, Xuepeng; Wu, Xiaohang; Wang, Qing; Zhou, Zhenzhen (Frontiers in Psychology, 2022)
In today’s VUCA era, especially during the COVID-19 pandemic, organizational resilience is vital to the survival and thriving of enterprises. Although there has been an increasing interest in organizational resilience, the effects from the entrepreneur perspective have received less attention. It is noteworthy that although deemed as an important positive psychological factor, entrepreneurial mindfulness has not been studied as an antecedent of organizational resilience. This paper examined how entrepreneurial mindfulness influences organizational resilience through the mediating mechanism of entrepreneurial resilience within a unique SME context of China during the crisis of Covid-19. We empirically analyzed a sample of 161 entrepreneurs managing small and medium-sized enterprises (SMEs) using SmartPLS software. The research findings indicated that entrepreneurial mindfulness is positively associated with organizational resilience and such relationship is partially mediated by entrepreneurial resilience. These findings convey important theoretical implications in this field of research as well as practical implications for SMEs in China or other countries with similar nature.